2016
DOI: 10.1038/srep24093
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbital effects in metal-dichalcogenide semiconducting monolayers

Abstract: Metal-dioxide & metal-dichalcogenide monolayers are studied by means of Density Functional Theory. For an accurate reproduction of the electronic structure of transition metal systems, the spin orbit interaction is considered by using fully relativistic pseudopotentials (FRUP). The electronic and spin properties of MX2 (M = Sc, Cr, Mn, Ni, Mo & W and X = O, S, Se & Te) were obtained with FRUP, compared with the scalar relativistic pseudopotentials (SRUP) and with the available experimental results. Among the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 88 publications
11
46
0
Order By: Relevance
“…In particular, it will aid band-gap and opto-electronic engineers to select the optimal TMDC for their device requirements. [61], 0.45 [22], 0.534 [86], 0.60 [91] 0.34 [53] 0.98 6.25 [53], [24] 0.06 ± 0. 0.00 Mono 0.51 [22], 0.51 [61], 0.561 [86], 0.51 [92] 0.54…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it will aid band-gap and opto-electronic engineers to select the optimal TMDC for their device requirements. [61], 0.45 [22], 0.534 [86], 0.60 [91] 0.34 [53] 0.98 6.25 [53], [24] 0.06 ± 0. 0.00 Mono 0.51 [22], 0.51 [61], 0.561 [86], 0.51 [92] 0.54…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the geometric and electronic structures of monolayer GeO, SnO, SnO 2 , MoO 2 , WO 2 , MoO 3 and NiO 2 were studied, [25][26][27][28][29][30] but the carrier mobilities of only MoO 3 and SnO monolayers were reported. 27,29 Here, the carrier transport properties of the MMOs are systematically investigated.…”
Section: Electronic Structures and Carrier Transport Properties Of Momentioning
confidence: 99%
“…10 Theoretically, the electronic properties of several monolayer metal oxides (MMOs), such as GeO, SnO, MoO 2 , WO 2 and MoO 3 , with different phases have been studied. [25][26][27][28][29][30] It was found that the bandgap of monolayer MOs decreases with increase of the thickness. Nonmagnetic layered metal oxides could be transformed to magnetic ones with both sides of the layer being functionalized.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, interesting characteristics may be found in 2D TMDs that were unnoticed or nonexistent in their bulk counterparts due to spin-orbit coupling or quantum confinement effects. [18][19][20][21][22][23] For example, when monolayer MoS 2 is cut away from the bulk, it shows an indirect-todirect bandgap transition, making it a promising material for electronic and optoelectronic applications. [24][25][26] Many other 2D TMD materials with outstanding properties and promising applications have also become hot topics of research in recent years.…”
mentioning
confidence: 99%